中国的城市住房制度 = Urban housing system in China - 桑卫京 Sang, Wei Jing (2008)
Basing on the discussion of urban housing character, this paper introduces and analyzes the evolvement of China's Urban Housing System (UHS) from 1949 and the UHS implemented at present.